Evaluation of serological assays available in a biosafety level 2 laboratory and their application for survey of Middle East respiratory syndrome coronavirus among livestock in Ethiopia - TERAMICHI, Takurou (J Vet Med Sci, 2019)
A serological survey of Middle East respiratory syndrome coronavirus (MERS-CoV) was conducted among dromedary camels and herbivorous animals sharing the same pasturage in Ethiopia. The pseudotyped vesicular stomatitis virus coated with the spike protein of MERS-CoV was used in virus neutralization (VN) tests performed in a biosafety level (BSL)-2 laboratory. The results were similar to those obtained from the VN test using live MERS-CoV and were more sensitive than the ELISA performed using synthetic MERS S1 fragment as the antigen as well as the competitive ELISA performed using a monoclonal antibody against MERS-CoV. According to the comprehensive results of the four types of serodiagnosis methods, positive antibodies were detected only in dromedary camels and the remaining herbivorous animals were not infected with the virus. Moreover, using the present procedure, serological tests for MERS-CoV can be conducted even in BSL 2 laboratory.